2000
DOI: 10.1292/jvms.62.681
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary Application of Ozone Therapy to Acute Clinical Mastitis in Dairy Cows.

Abstract: ABSTRACT. The infusion of ozone into the inflamed quarter of cows with clinical mastitis was performed and the efficacy of ozone therapy was evaluated. Ozone was infused into the inflamed quarter via a teat canal using ozone gas generating equipment. Nineteen Holstein cows with acute clinical mastitis were divided into two groups: 15 cows treated with ozone therapy, and 4 cows treated with antibiotic therapy. Systemic and local clinical signs, California Mastitis Test scores, the mastitis causing pathogens, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 12 publications
1
30
0
11
Order By: Relevance
“…The mechanism of ozone sterilization involves destruction of the microbial cell membrane, and its sterilization power is proportionate to contact time and density. Many studies have documented use of ozone administration into the blood or body as a medical treatment [5], and some studies have documented it use in veterinary medicine [9,11]. Use of ozone as a therapy for acute mastitis does not produce serious side effects such as endotoxin shock, and the cure rate of acute mastitis with ozone therapy is higher than that with the conventional treatment method [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of ozone sterilization involves destruction of the microbial cell membrane, and its sterilization power is proportionate to contact time and density. Many studies have documented use of ozone administration into the blood or body as a medical treatment [5], and some studies have documented it use in veterinary medicine [9,11]. Use of ozone as a therapy for acute mastitis does not produce serious side effects such as endotoxin shock, and the cure rate of acute mastitis with ozone therapy is higher than that with the conventional treatment method [9].…”
mentioning
confidence: 99%
“…The use of ozone is spreading as a treatment for masititis [9], particularly because of the high cure rate of coliform mastitis with intramammary application of ozone gas. It has been reported that compared with antibiotic treatment, ozone treatment induces release of smaller amounts of endotoxin into milk and does not lead to iatrogenic endotoxin shock, which is a negative effect of antibiotic treatment [12]; our in vitro results support this study.…”
mentioning
confidence: 99%
“…It is well recognized that ozone has sterilization capabilities and is applied in various fields [17]. It is being increasingly used as a treatment tool in mastitis [9], especially for the treatment of coliform mastitis, where intramammary application of ozone gas is used due to its high cure rate. It was reported that treatment with ozone released fewer endotoxins in the milk than treatment with antibiotics; further, no iatrogenic endotoxic shock occurred as an adverse effect, unlike that in the case of antibiotic treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of ozone therapy could be attributable to increase in leukocytic function and increased respiratory burst. Ozone therapy can be preferred over antibiotic therapy in treating clinical mastitis as no milk withdrawal time is required with ozone therapy (Ogata & Nagahata, 2000). However, it is not clear whether ozone functions by killing the pathogen or by improving the host defence mechanism.…”
Section: Clinical Mastitis In Maresmentioning
confidence: 99%